Análise da resposta dinâmica de vigas mistas biapoiadas com perfil tubular retangular de aço para diferentes configurações - Damia Carina Dias do Carmo (2017)
Experimental and analytical results about dynamics response of beams with different configurations and rectangular sections are presented and compared in this study. Six different configurations of composite beams were studied: steel tubular beam without concrete; concretefilled steel tubular beam with and without internal surface preparation; concrete-filled steel tubular beam, without internal surface preparation and steel reinforcement in one and two layers; concrete-filled steel tubular beam, without internal surface preparation, with steel reinforcement drawn in two layers and with collaborating slab superimposed. The experimentaltest used was "impact test, the data were processed in Matlab and shown using Frequency Response Function (FRF) curves. The Mode Indicator Function (MIF) method was also used in order to bring together FRF values obtained in different measurements for determination ofnatural frequencies. From the FRFs curves it was possible to obtain the damping factor of the first natural frequency of each beam, by the method of "half-power bandwidth". The results showed a good correlation between the fundamental frequencies obtained through the experimental and analytical procedures. It has also been demonstrated that there is a more significant difference in the steel tubular beam without concrete dynamic response compared with the others. The variations in the other beams configuration do not generate a significant influence on their dynamic response.